Intravenous Allogeneic Mesenchymal Stem Cells for Nonischemic Cardiomyopathy: Safety and Efficacy Results of a Phase II-A Randomized Trial. Issue 2 (20th January 2017) - Butler, Javed; Epstein, Stephen E.; Greene, Stephen J.; Quyyumi, Arshed A.; Sikora, Sergey; Kim, Raymond J.; Anderson, Allen S.; Wilcox, Jane E.; Tankovich, Nikolai I.; Lipinski, Michael J.; Ko, Yi-An; Margulies, Kenneth B.; et al.
Abstract : Rationale: : Potential benefits of mesenchymal stem cell (MSC) therapy in heart failure may be related to paracrine properties and systemic effects, including anti-inflammatory activities. If this hypothesis is valid, intravenous administration of MSCs should improve outcomes in heart failure, an entity in which excessive chronic inflammation may play a pivotal role. Objective: : To assess the safety and preliminary efficacy of intravenously administered ischemia-tolerant MSCs (itMSCs) in patients with nonischemic cardiomyopathy. Methods and Results: : This was a single-blind, placebo-controlled, crossover, randomized phase II-a trial of nonischemic cardiomyopathy patients with left ventricular ejection fraction ⩽40% and absent hyperenhancement on cardiac magnetic resonance imaging. Patients were randomized to intravenously administered itMSCs (1.5×10 6 cells/kg) or placebo; at 90 days, each group received the alternative treatment. Overall, 22 patients were randomized to itMSC (n=10) and placebo (n=12) at baseline. After crossover, data were available for 22 itMSC patients. No major differences in death, hospitalization, or serious adverse events were noted between the 2 treatments. Change from baseline in left ventricular ejection fraction and ventricular volumes was not significantly different between therapies. Compared with placebo, itMSC therapy increased 6-minute walk distance (+36.47 m, 95% confidence interval 5.98–66.97; P =0.02) and improved Kansas City Cardiomyopathy clinical summary (+5.22, 95% confidence interval 0.70–9.74; P =0.02) and functional status scores (+5.65, 95% confidence interval −0.11 to 11.41; P =0.06). The data demonstrated MSC-induced immunomodulatory effects, the magnitude of which correlated with improvement in left ventricular ejection fraction. Conclusions: : In this pilot study of patients with nonischemic cardiomyopathy, itMSC therapy was safe, caused immunomodulatory effects, and was associated with improvements in health status and functional capacity. Clinical Trial Registration: : URL:http://www.clinicaltrials.gov . Unique identifier: NCT02467387. Abstract : Supplemental Digital Content is available in the text.